2014
DOI: 10.1016/j.egypro.2014.11.1181
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Insulation of Abandoned Oil Wells Reused for Geothermal Power Generation

Abstract: Geothermal power generation from abandoned oil wells is a new way to utilize geothermal energy. An analysis model based on transient formation heat transfer is presented in this paper. Through the double-pipe heat exchanger, R143a is used as working fluid for obtaining geothermal energy from abandoned oil wells. The influence of insulation on heat transfer from the recovery well to the injection well is investigated. The result shows that the outlet temperature of fluid leaving the recovery well gradually incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…There has been several studies reported by researchers over the globe where the potential of geothermal energy generation from depleted wells have been investigated experimentally and theoretically [1][2][3][4][5][6][7][8][9][10][11][12][13]. These studies have demonstrated the potential as well as the readiness level of the technologies needed for utilization of geothermal energy from depleted wells.…”
Section: Geothermal Drilling Technology: Opportunities and Challengesmentioning
confidence: 99%
“…There has been several studies reported by researchers over the globe where the potential of geothermal energy generation from depleted wells have been investigated experimentally and theoretically [1][2][3][4][5][6][7][8][9][10][11][12][13]. These studies have demonstrated the potential as well as the readiness level of the technologies needed for utilization of geothermal energy from depleted wells.…”
Section: Geothermal Drilling Technology: Opportunities and Challengesmentioning
confidence: 99%
“…Cui et al (2017) and Bu et al (2012) proposed a method for geothermal exploitation in order to calculate the heat mining rate and the relationship between the geothermal water and heat production. With respect geothermal power generation, Cheng et al (2014) analysed the heat production from geothermal water flows using heat exchangers. Aliyu and Chen (2017) applied an approach for the long-term development of geothermal heating production.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Various fluids except water were assessed (e.g., CO 2 and organic working media) [23][24][25][26][27]. Cheng et al (2013 analyzed the performance of different organic fluids used as the heatcarrying medium for geothermal power generation and discussed the influence of the thermal insulation performance of tubing on the heat mining effect under the condition that R134a was used as the heat-carrying fluid [26,28,29]. Davis and Michaelides (2009) used isobutane as the heat-carrying fluid to simulate geothermal power generation from abandoned oil wells.…”
Section: Introductionmentioning
confidence: 99%